2021
DOI: 10.4085/1062-6050-370-20
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Injuries in National Collegiate Athletic Association Men's Soccer: 2014–2015 Through 2018–2019

Abstract: Context The National Collegiate Athletic Association has sponsored men's soccer programs since 1959, and the popularity of the sport has grown over time. Background Routine examinations of athlete injuries are important for identifying emerging temporal patterns. Methods Exposure and injury data collected in the National Collegiate Athletic Association Injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…These athletes are also more likely to experience more severe symptoms and can take longer to recover 9. NCAA-ISP studies which replicated our included studies in male soccer, basketball, ice hockey and lacrosse found only soccer posed a notably higher overall SRC risk for females 56–59. However, one US collegiate study found higher match SRC rates for females than males in each of these sports 35.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…These athletes are also more likely to experience more severe symptoms and can take longer to recover 9. NCAA-ISP studies which replicated our included studies in male soccer, basketball, ice hockey and lacrosse found only soccer posed a notably higher overall SRC risk for females 56–59. However, one US collegiate study found higher match SRC rates for females than males in each of these sports 35.…”
Section: Discussionsupporting
confidence: 70%
“…9 NCAA-ISP studies which replicated our included studies in male soccer, basketball, ice hockey and lacrosse found only soccer posed a notably higher overall SRC risk for females. [56][57][58][59] However, one US collegiate study found higher match SRC rates for females than males in each of these sports. 35 A systematic review of SRCs in team contact sports also reported far lower match rates for male rugby union (2.16-8.93 per 1000 AE hours) than reported for females in the current study.…”
Section: Open Accessmentioning
confidence: 99%
“…These findings are largely in alignment with previous reports, 34 although the differential prevalence of player-contact lateral ankle sprains between men's and women's sports was noteworthy and warrants further attention. These findings provide a critical update to the existing empirical evidence surrounding the most common injury reported among NCAA athletes (of note, lateral ankle sprains accounted for ~8% of all injuries reported to the NCAA ISP during the study period) 5,6,24,27 and offer avenues for further targeted evaluations and therapeutic interventions.…”
Section: Time Lossmentioning
confidence: 70%
“…Lateral ligament complex tears (or lateral ankle sprains) have been reported to account for most sports-related ankle sprains. 13 Previous studies have shown ankle sprains to be a prevalent injury among athletes participating in National Collegiate Athletic Association (NCAA) competition, [5][6][7]24,27 and recent evidence suggests that lateral ankle sprains are common injuries across field-and court-based NCAA sports. 34 Although injury prevention efforts that include balance and proprioceptive training have been shown to be effective in mitigating the risk of ankle sprain in different settings, 2,10,35 advances in prevention efforts depend on routine and systematic epidemiological investigations aimed at capturing the burden of this injury in various athlete populations.…”
mentioning
confidence: 99%
See 1 more Smart Citation